Canonical correlation between longitudinal dimensionality of the body and success in performing dancing structures with preschool children - Stanišić Irena R. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
The research had been carried out with the aim to investigate relations of longitudinal dimensionality of the body and success in performing dancing structures with preschool children. The specimen consisted of 180 preschool children aged 6 (100 boys and 80 girls). For assessing longitudinal dimensionality of the body the following parameters were applied: body height, body height in sitting position, leg length, arm length, lower leg length and foot length. For assessing the success in performing dancing structures the following metric instruments were applied: Waltz steps, Polka steps, Moravac steps. The criterion was the mark for evaluating the success in performing the given dancing structures. The 'judges' evaluated the performance for each child with marks from 1 to 5. In order to establish the relation between the variables of dimensionality of the body and success in performing dancing structures, the canonical correlation analysis was applied. Based on the results of the degree of significance, it was established that there is not a statistically significant connection between the two sets of variables with the girls. Based on canonical correlation with the boys, the general connection of longitudinal dimensionality of the body and performing dancing structures was established.